2016
DOI: 10.1590/0004-282x20150213
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery stenting in the context of endovascular treatment of acute ischemic stroke

Abstract: Intravenous thrombolysis (IVT) with recombinant tissue plasminogen activator (r-tPA) is the standard treatment for acute ischemic stroke (AIS) within the first four and a half hours of symptom onset 1 , and five recent clinical trials demonstrated better clinical outcomes when mechanical thrombectomy with stentrievers were performed as an adjunctive treatment to IVT for patients presenting large vessel occlusions within the first six hours of symptom onset 2,3,4,5 . However, those trials lacked sufficient powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This updated meta-analysis, including our registry data, reports a positive association between emergent carotid stenting after MT and successful reperfusion Overall (I 2 = 71.11%, P = 0.00) Lockau et al [13] Marnat et al [14] Lescher et al [12] de Lucena et al [9] Fahed et al [10] Steglich-Arnholm [20] Rangel-Castilla et al [17] Heck and Brown [11] Cohen et al [8] Sallustio et al [18] Mpotsaris et al [16] Author Stampfl et al [19] Our series Maurer el al. [15] Rangel-Castilla et al [17] Fahed et al [10] Stampfl et al [19] de Lucena et al [9] Heck and Brown [11] Lockau et al [13] Mpotsaris et al [16] Our series Lescher et al [12] Sallustio et al [18] Marnat et al [14] Steglich-Arnholm [20] Author…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…This updated meta-analysis, including our registry data, reports a positive association between emergent carotid stenting after MT and successful reperfusion Overall (I 2 = 71.11%, P = 0.00) Lockau et al [13] Marnat et al [14] Lescher et al [12] de Lucena et al [9] Fahed et al [10] Steglich-Arnholm [20] Rangel-Castilla et al [17] Heck and Brown [11] Cohen et al [8] Sallustio et al [18] Mpotsaris et al [16] Author Stampfl et al [19] Our series Maurer el al. [15] Rangel-Castilla et al [17] Fahed et al [10] Stampfl et al [19] de Lucena et al [9] Heck and Brown [11] Lockau et al [13] Mpotsaris et al [16] Our series Lescher et al [12] Sallustio et al [18] Marnat et al [14] Steglich-Arnholm [20] Author…”
Section: Resultsmentioning
confidence: 79%
“…Fifty-seven articles were reviewed at full-text level, of which 13 studies were selected for final analysis, including four studies included in our previous review and matching our inclusion criteria ( Fig. 1) [8][9][10][11][12][13][14][15][16][17][18][19][20]. A total of 590 proximal anterior circulation stroke patients [mean age 66.4 years; 65% (n = 382) men] presenting with ECD were included.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, modern devices permit faster access and easier navigation due to a more flexible profile 20 . Recent prospective trials have shown the clinical benefit of endovascular therapy, providing high-level evidence that has changed the guidelines of acute stroke therapy to recommend endovascular therapy with a stent retriever over intra-arterial fibrinolysis alone as first-line therapy 10,19,20,21 . However, its use during transprocedural thromboembolic events is still not validated, as the passage of the device over the coil mass could displace it and occlude the parent vessel.…”
Section: Discussionmentioning
confidence: 99%